2021
DOI: 10.1155/2021/2231371
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Safe Food Temperature among Restaurant Supervisors in Dammam, Saudi Arabia

Abstract: Foodborne diseases are usually caused by consuming foods that are stored at an inappropriate temperature. This study aims to evaluate the knowledge of safe food temperature control among restaurant supervisors of Dammam city, Saudi Arabia. A cross-sectional study was carried out during January 2019 to May 2019. A close-ended questionnaire was used to assess knowledge and source of information about food temperature control from restaurant supervisors. The response rate of the study was 97 (80.8%). Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our previous study conducted with restaurant managers revealed that they had a fair‐to‐good level of knowledge about the internal temperature of cooked meat and the best method to check for safe cooking temperature, that is, using a thermometer and a cold food storage temperature (Al‐Mohaithef et al, 2021 ). Therefore, the employment of a well‐qualified manager in the restaurant can help in effective time temperature control management.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study conducted with restaurant managers revealed that they had a fair‐to‐good level of knowledge about the internal temperature of cooked meat and the best method to check for safe cooking temperature, that is, using a thermometer and a cold food storage temperature (Al‐Mohaithef et al, 2021 ). Therefore, the employment of a well‐qualified manager in the restaurant can help in effective time temperature control management.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature stability of the crude Actinomycetes extracts were incubated in a water bath for 24 h at 4 °C, 25 °C, 35 °C, 45 °C, 55 °C, and 65 °C. The post-treatment extracts were tested to determine their ability to inhibit and destroy biofilms [28][29][30]66 . For biofilm inhibition test, 100 µL of crude extracts and 100 µL of bacterial cultures (OD 600 = 0.132) were transferred into 96-well microtiter plates then incubated at pathogens' respective temperatures for 24 h. Meanwhile, for biofilm destruction test, 100 µL of bacterial culture were transferred into 96-well microtiter plates then incubated at pathogens' respective temperature.…”
Section: Methodsmentioning
confidence: 99%